2013
DOI: 10.1021/la304658e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Counterions on the Shape, Hydration, and Degree of Order at the Interface of Cationic Micelles: The Triflate Case

Abstract: Specific ion effects in surfactant solutions affect the properties of micelles. Dodecyltrimethylammonium chloride (DTAC), bromide (DTAB), and methanesulfonate (DTAMs) micelles are typically spherical, but some organic anions can induce shape or phase transitions in DTA(+) micelles. Above a defined concentration, sodium triflate (NaTf) induces a phase separation in dodecyltrimethylammonium triflate (DTATf) micelles, a phenomenon rarely observed in cationic micelles. This unexpected behavior of the DTATf/NaTf sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
59
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(80 citation statements)
references
References 86 publications
19
59
2
Order By: Relevance
“…2 Additionally, the hydration behavior of the counterions has drastic effects on micelle size and shape. 3…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Additionally, the hydration behavior of the counterions has drastic effects on micelle size and shape. 3…”
Section: Introductionmentioning
confidence: 99%
“…The micellization of surfactants is regarded as a useful model process for their investigation. To understand these effects on a molecular level, recent studies attempted to explore the complete atomistic structure of a micelle and its surroundings in solution. It was found that the hydrophobic core of a micelle is surrounded by a highly corrugated surface containing hydrated nonpolar cavities, whose depth increases with increasing surfactant chain length . Additionally, the hydration behavior of the counterions has drastic effects on micelle size and shape …”
Section: Introductionmentioning
confidence: 99%
“…The properties of the interface of cationic amphiphiles, which contain a quaternary ammonium head group, can be significantly modified by changing the counterion (Lima et al 2013). Anions containing a more hydrophobic group, like triflates, alkyl carboxylates, aromatic carboxylic acids and aromatic sulfonic acids, can lead to viscoelastic solutions with different aggregates structures, such as rodlike, threadlike, wormlike or polymer-like micelles.…”
Section: Shape Changes and Interface Compositionmentioning
confidence: 99%
“…The micelle properties can be affected by surfactant concentration, salt, counterions, and temperature [62][63][64]. For the nonionic surfactant, Triton X-100, the aggregation number and radius of its micelles increase with increasing ionic strength, with the micelles becoming larger and more diffuse in structure [64].…”
Section: Hydration Of Collector Aggregatesmentioning
confidence: 99%